Linguistic Cues Enhance the Learning of Perceptual Cues - Yoshida, Hanako (2005)
When language is correlated with regularities in the world, does it enhance the learning of these regularities? This question lies at the core of both notions of linguistic bootstrapping in children and the Whorfian hypothesis. Support for an affirmative answer is provided in an artificial-noun-learning task in which 2-year-old children were taught to distinguish categories of solid and nonsolid things with and without supporting correlated linguistic cues.